CTLs: Killers of intracellular bacteria - Tian, Li; Zhou, Wei; Wu, Xianwei; Hu, Zhuannan; Qiu, Lei; Zhang, Huiyong; Chen, Xue; Zhang, Shaoyan; Lu, Zhenhui (Frontiers in Cellular and Infection Microbiology, 2022)
Many microbial pathogens have evolved a range of capabilities to evade host immune defense mechanisms and to survive and multiply in host cells. The presence of host intracellular bacteria makes it difficult for specific antibodies to function. After the intracellular bacteria escape the attack of the innate immune system, such as phagocytes, they survive in cells, and then adaptive immunity comes into play. Cytotoxic T lymphocytes (CTLs) play an important role in eliminating intracellular bacteria. The regulation of key transcription factors could promote CD4+/CD8+ T cells to acquire cytolytic ability. The TCR-CD3 complex transduces activation signals generated by TCR recognition of antigen and promotes CTLs to generate multiple pathways to kill intracellular bacteria. In this review, the mechanism of CD4/CD8 CTLs differentiation and how CD4/CD8 CTLs kill intracellular bacteria are introduced. In addition, their application and prospects in the treatment of bacterial infections are discussed.